3D bioprinting of nanoparticle-laden hydrogel scaffolds with enhanced antibacterial and imaging properties - Andrea S. Theus; Liqun Ning; Gabriella Kabboul; Boeun Hwang; Martin L. Tomov; Christopher N. LaRock; Holly Bauser-Heaton; Morteza Mahmoudi; Vahid Serpooshan (iScience, 2022)
Summary: Biomaterial-associated microbial contaminations in biologically conducive three-dimensional (3D) tissue-engineered constructs have significantly limited the clinical applications of scaffold systems. To prevent such infections, antimicrobial biomaterials are rapidly evolving. Yet, the use of such materials in bioprinting-based approaches of scaffold fabrication has not been examined. This study introduces a new generation of bacteriostatic gelatin methacryloyl (GelMA)-based bioinks, incorporated with varying doses of antibacterial superparamagnetic iron oxide nanoparticles (SPIONs). The SPION-laden GelMA scaffolds showed significant resistance against the Staphylococcus aureus growth, while providing a contrast in magnetic resonance imaging. We simulated the bacterial contamination of cellular 3D GelMA scaffolds in vitro and demonstrated the significant effect of functionalized scaffolds in inhibiting bacterial growth, while maintaining cell viability and growth. Together, these results present a new promising class of functionalized bioinks to 3D bioprint tissue-engineered scaffold with markedly enhanced properties for the use in a variety of in vitro and clinical applications.